2016 49th Hawaii International Conference on System Sciences (HICSS) 2016
DOI: 10.1109/hicss.2016.612
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Border: A Comparative Literature Review on Communication Practices for Agile Global Outsourced Software Development Projects

Abstract: Software development is increasingly heading in the direction of combining agile software development practices and outsourcing software development to external vendors worldwide. The resulting agile global outsourced software development (AGOSD) projects are characterized by applying agile methods to distributed environments, which results in several problems for collaboration and coordination. Specifically, communication between the project participants has been found to be a major challenge in distributed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…We conducted a recent, comparative literature review on communication in distributed agile software development projects and communication in AGOSD projects [29]. For example, several studies identified the practice of "face-to-face" communication as essential for agile development endeavors to exchange implicit knowledge and provide direct feedback between the participants [30][31][32].…”
Section: Communication In Agile Developmentmentioning
confidence: 99%
“…We conducted a recent, comparative literature review on communication in distributed agile software development projects and communication in AGOSD projects [29]. For example, several studies identified the practice of "face-to-face" communication as essential for agile development endeavors to exchange implicit knowledge and provide direct feedback between the participants [30][31][32].…”
Section: Communication In Agile Developmentmentioning
confidence: 99%
“…Most studies have emphasized the need for “trust” among members to enhance communication. One of these reasons is different cultural background among team members that leads to effective communication ( Dreesen et al., 2016 ). Social relationships heavily influence the effectiveness of communication.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Employees often align themselves with their employer. Further research could concentrate on a higher diversity of practice partners (e.g., different branches and providers with internal as well as external clients) and in a more global context [30].…”
Section: Limitationsmentioning
confidence: 99%